Strategi Pemanfaatan Media Sosial Instagram Sebagai Media Komunikasi Pemasaran (GEMA EKONOMI, 2023)
The Social media growth today seems inseparable in daily basis. Social media also needed for business actors. Along with the growth of local brands, all business actors rely on social media to introduce and promote their product. It is related to this research "Strategies for utilizing Social Media, Instagram as a Marketing Communication Media (Descriptive Study, Skincare Somethinc.) The research uses a Qualitative method with a Desriptive approach. The results of research show that Somethinc implements SOSTAC as their marketing communication strategy, they also use korean group member, NCT. They use story telling techniques when promote their products on their social media.